(untitled) (Global Journal of Medical Research, 2020)
In Paraguay, as a bilingual country and with a characteristic historical context, it has always been considered a challenge to reach the Guaran#xED;-speaking population, especially those from the most vulnerable sectors, through the use of tools that bridge the gap in the language barrier in care services in general. By translating the epilepsy diagnostic questionnaire aimed at its use in primary care, the aim is to bring to the medical professional a useful element in clinical practice that also provides data of diagnostic value and treatment guide. In this work, the validation of the questionnaire, originally conceived in Spanish, was carried out, distinguishing some idiomatic aspects that add richness to the clinical history in epilepsy and define the therapeutic aspect, providing the medical professional with a material of practical use and easy to apply in clinical practice daily.